A projeção internacional do Brasil para a África de 2003 a 2010 - Infaga, Iabna (2017)
This dissertation analyses the evolution of the Brazilian foreign policy about international cooperation of Brazil to Africa, in the period of 2003 to 2010, understanding the reasons that stimulated this process. The development of this research is anchored in two main axes, which are, the South-South Cooperation (SSC) and the operation of Brazilian companies in Africa, specially Angola and Mozambique that are two countries with Portuguese as official language used for the deepening of this research. This article studies of international projection of Brazil to Africa, mainly in Angola and Mozambique, what is a result of technical cooperation and the performance of companies. The main results found in this research, are two: first, that Brazil – in the SSC scope - implemented extremely important projects for the socioeconomic development of those two African countries. On the other side, the performance of Brazilian companies in those countries, even though they represent some positive economic impact, do not always corroborate with the expectations launched by the political and diplomatic discourse that concern with the establishment of a good image of Brazil in the African continent. This research was developed based on bibliographic and documental sources, besides the investigative journalism.